Natural Products Attenuate Pi3k/Akt/Mtor Signaling Pathway: A Promising Strategy in Regulating Neurodegeneration - Echeverria-Morgado, J (Elsevier GmbH, 2021)
Background: As common, progressive, and chronic causes of disability and death, neurodegenerative diseases (NDDs) significantly threaten human health, while no effective treatment is available. Given the engagement of multiple dysregulated pathways in neurodegeneration, there is an imperative need to target the axis and provide effective/multi-target agents to tackle neurodegeneration. Recent studies have revealed the role of phosphoinositide 3-kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) in some diseases and natural products with therapeutic potentials. Purpose: This is the first systematic and comprehensive review on the role of plant-derived secondary metabolites in managing and/or treating various neuronal disorders via the PI3K/Akt/mTOR signaling pathway. Study design and methods: A systematic and comprehensive review was done based on the PubMed, Scopus, Web of Science, and Cochrane electronic databases. Two independent investigators followed the PRISMA guidelines and included papers on PI3K/Akt/mTOR and interconnected pathways/mediators targeted by phytochemicals in NDDs. Results: Natural products are multi-target agents with diverse pharmacological and biological activities and rich sources for discovering and developing novel therapeutic agents. Accordingly, recent studies have shown increasing phytochemicals in combating Alzheimer s disease, aging, Parkinson s disease, brain/spinal cord damages, depression, and other neuronal-associated dysfunctions. Amongst the emerging targets in neurodegeneration, PI3K/Akt/mTOR is of great importance. Therefore, attenuation of these mediators would be a great step towards neuroprotection in such NDDs. Conclusion: The application of plant-derived secondary metabolites in managing and/or treating various neuronal disorders through the PI3K/Akt/mTOR signaling pathway is a promising strategy towards neuroprotection. © 2021